2020
DOI: 10.1186/s12870-020-02780-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals, phytochemicals, and radical quenching ability of selected drought-tolerant advance lines of vegetable amaranth

Abstract: Background Vegetable amaranth is a source of natural phytopigments and functional components of the commercial food industry for sustainable health benefits across the globe. It is guessed that recently identified amaranth (drought-tolerant) genotypes may contain ample phytopigments and phytochemicals suitable to extract juice as drinks. Hence, phytopigments and phytochemicals content of amaranth were assessed in detail for suitability as drinks to feed the phytochemicals deficient community ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 67 publications
0
41
1
Order By: Relevance
“…The leaves possessed higher TFC content than the TPC. Leaves of different amaranth species also had higher TPC, TFC and DPPH antioxidant capacity [36,37]. Mean values in the same column (organic versus conventional) are significantly different at p < 0.05 (Independent t-test).…”
Section: Antioxidant Activities Of Passiflora Quadrangularismentioning
confidence: 96%
“…The leaves possessed higher TFC content than the TPC. Leaves of different amaranth species also had higher TPC, TFC and DPPH antioxidant capacity [36,37]. Mean values in the same column (organic versus conventional) are significantly different at p < 0.05 (Independent t-test).…”
Section: Antioxidant Activities Of Passiflora Quadrangularismentioning
confidence: 96%
“…The authors emphasized that global metabolomics has potential for identification of compounds within species and is a much-needed avenue in the genus Dioscorea [ 19 , 20 ]. A literature survey demonstrated that different cultivars within a species have pronounced variations in terms of metabolomic profiles e.g., Amaranthus gangeticus [ 21 , 22 , 23 ], A. hypochondriacus [ 24 ] drought-tolerant A. tricolor [ 22 , 25 , 26 ], stem amaranth [ 27 ], A. blitum [ 28 ], green morph amaranth [ 29 ], weedy amaranth [ 30 ], and red morph amaranth [ 31 ]. Similarly, it has been reported that the secondary metabolite profiles of Dioscorea spp.…”
Section: Introductionmentioning
confidence: 99%
“…The Mg, Cu and P levels in nibai are the highest, when compared to spinach and fiddlehead fern. Mg, Cu and P were much higher than vegetable amaranth (Sarker and Oba, 2020e). Zn levels in nibai are similar to spinach, but both are significantly lower than fiddlehead.…”
Section: Minerals Vitamins and β-Carotenementioning
confidence: 76%
“…Dietary fiber can also help to reduce cholesterol levels, prevent obesity and chronic diseases (Patil et al, 2009). Dietary fiber significantly contributed to the cure of constipation, digestibility, and palatability Sarker and Oba, 2020d;Sarker and Oba, 2020e). Nibai has a high content of protein, along with a low carbohydrate content, making it a potentially healthy food plant for people looking to reduce carbohydrate intake.…”
Section: Results and Discussion Nutrient Composition And Dietary Fibermentioning
confidence: 99%